2017
DOI: 10.4172/2155-6148.1000743
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Measurement of Intraoperative Blood Loss Improves Prediction of Postoperative Hemoglobin Levels

Abstract: Background: Restrictive red cell transfusion is preferable to liberal transfusion in most clinical situations. However, intraoperative transfusion decisions are challenging due to uncertainty about the amount and rate of bleeding, the poor correlation of hemoglobin levels with blood loss and the effects of anesthetics on blood volume and physiologic responses. Clinicians frequently use hemoglobin levels to guide transfusion. While these "triggers" assume that the patient is normovolemic, they are often applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…By entering the preoperative Hb-level, the blood loss can then be calculated. In the studies analyzed, high degrees of correlation with the reference blood volumes were found [ 22 , 24 , 26 28 , 39 , 67 , 68 , 70 , 83 ] (For a detailed description of the various studies, please refer to supplement 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By entering the preoperative Hb-level, the blood loss can then be calculated. In the studies analyzed, high degrees of correlation with the reference blood volumes were found [ 22 , 24 , 26 28 , 39 , 67 , 68 , 70 , 83 ] (For a detailed description of the various studies, please refer to supplement 6).…”
Section: Resultsmentioning
confidence: 99%
“…The risk of bias due to confounders was increased in the majority of the studies. The selection of participants in study groups showed an increased risk of bias in four studies [19][20][21][22] and an unclear risk of bias in two studies [23,24]. The documentation and endpoint assessment were adequately described in most of the studies.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…6 Histogram of the differences The histogram shows frequency of differences between visually estimated (V-EBL) for canister and reference blood loss we were able to identify an advantage in measurement of blood volume in sponges by technically supported methods such as colorimetric blood loss estimation. Experimental studies of this system have also been published for canisters [12][13][14][15][16][17][18]. With colorimetric blood loss estimation, blood volume in sponges or canisters can be measured in real time.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it provides real-time information on blood loss and potentially improves the treatment of bleeding patients and targeted haemotherapy. So far, colorimetric blood loss estimation is only capable of analysing white sponges [25][26][27][28][29].…”
Section: Plos Onementioning
confidence: 99%